2002
DOI: 10.1074/jbc.m206830200
|View full text |Cite
|
Sign up to set email alerts
|

8-(3-Chlorostyryl)caffeine May Attenuate MPTP Neurotoxicity through Dual Actions of Monoamine Oxidase Inhibition and A2A Receptor Antagonism

Abstract: The neurodegeneration of Parkinson's disease (PD) 1 targets dopaminergic neurons that project to the striatum (1). In PD the progressive loss of striatal dopamine leads to a progressive deterioration in motor function. Despite the availability of dopamine-replacement strategies that generally offer considerable symptomatic relief early in the disease, as yet no therapy has been shown to slow the underlying neurodegenerative process.Adenosine A 2A receptor antagonists recently have attracted attention as potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 22 publications
0
59
0
1
Order By: Relevance
“…In that experiment, a low single dose of CSC and ZM 241385 either inhibited or did not alter, respectively, generation of hydroxyl radical by L-DOPA; on the other hand, in high dose they were equipotent toward the elevation of hydroxyl radical levels produced by L-DOPA. The suppressing effect of low single dose CSC on hydroxyl radical formation appears to be related to an inhibition of DA metabolism, as CSC has been shown to be a potent competitive monoamine oxidase-B (MAO-B) inhibitor, its K i being 100 nM (Chen et al 2002). Conversely, ZM 241385, which is devoid of MAO-B inhibitory properties, was ineffective in influencing either the L-DOPA-induced DA release or hydroxyl radical production when it was administered acutely in low dose.…”
Section: Discussionmentioning
confidence: 98%
“…In that experiment, a low single dose of CSC and ZM 241385 either inhibited or did not alter, respectively, generation of hydroxyl radical by L-DOPA; on the other hand, in high dose they were equipotent toward the elevation of hydroxyl radical levels produced by L-DOPA. The suppressing effect of low single dose CSC on hydroxyl radical formation appears to be related to an inhibition of DA metabolism, as CSC has been shown to be a potent competitive monoamine oxidase-B (MAO-B) inhibitor, its K i being 100 nM (Chen et al 2002). Conversely, ZM 241385, which is devoid of MAO-B inhibitory properties, was ineffective in influencing either the L-DOPA-induced DA release or hydroxyl radical production when it was administered acutely in low dose.…”
Section: Discussionmentioning
confidence: 98%
“…They found that repeated and "chronic" coadministration of (E)-8-(3-chlorostyryl) caffeine, which is a potent monoamine oxidase B inhibitor as well as A 2A antagonist (Chen et al, 2002), and MPEP synergistically alleviated motor deficits in the 6-OHDA-lesioned rat model of PD. In the present study, a similar synergy was demonstrated after "acute" coadministration of A 2A and mGlu5 antagonists, the specificities of which for their receptors were definitively demonstrated using respective KO mice (Fig.…”
Section: Synergistic Antiparkinsonian Actions Of a 2a And Mglu5 Antagmentioning
confidence: 99%
“…As part of an investigation to determine the mechanism by which CSC protects mice against the neurotoxic effects of MPTP, it was discovered that, in addition to being a potent and selective A 2A antagonist, CSC also acted as a highly potent, competitive, and reversible inhibitor of MAO-B. 26 This finding has raised the possibility of designing dual-target-directed drugs that block at both A 2A receptors and at MAO-B. To determine the structural requirements necessary for methylxanthines to act as MAO-B inhibitors, various substituted methylxanthines were evaluated as MAO-B inhibitors.…”
Section: Methylxanthines As Dual-target-directed Drugsmentioning
confidence: 99%